Fabrication of a novel acrylate polymer bearing chalcone and amide groups and investigation of its thermal and isoconversional kinetic analysis - Biryan, Fatih; Pihtili, Guzin (Springer, 2020)
The aim of the article was to examine the thermal degradation, thermal decomposition kinetics and dielectric behavior of novel poly(APHP-Am-Ac). For this purpose, the novel monomer, 4-(3-(4-acetamidophenyl)-3-oxoprop-1-en-1-yl)phenyl acrylate (APHP-Am-Ac), was synthesized from 1-(4-aminophenyl)-3-(4-hydroxyphenyl) prop-2-en-1-one (APHP) and acetic anhydride reaction. The homopolymer P(APHP-Am-Ac) was prepared by free radical polymerization within dimethylformamide at 80 degrees C. The presence of rigid and bulky chalcone units in polymer side chains significantly improved the solubility of polyamides, giving them an amorphous nature and good thermal stability. The structural characterization of homopolymer was accomplished using FT-IR and NMR techniques. The thermal stability and degradation features of homopolymer have been performed by using TG analysis and FT-IR during partial degradation at different temperatures. The glass transition temperature of homopolymer was determined by DSC analysis. For thermal decomposition kinetics of poly(APHP-Am-Ac), Flynn-Wall-Ozawa and Kissinger methods were applied to thermogravimetric curves and apparent activation energies (E-a) calculated from these two methods. According to FWO, the activation energy (E-a) of the first step and the second step was found as: 157.78 kJ mol(-1) and 151.81 kJ mol(-1), respectively. For Kissinger's model, E-a was calculated as 154.3 kJ mol(-1) and 142.83 kJ mol(-1), respectively. The dielectric and conductivity measurements of homopolymer were investigated by impedance analyzer technique in a range of 10 Hz-20 kHz frequency at different temperatures (from 25 to 120 degrees C). The results have been plotted as a function of frequency and temperatures. The values increased significantly with temperature.
2nd International Conference on Physical Chemistry and Functional Materials (PCFM) -- JUN 25-27, 2019 -- Cappadocia, TURKEY
Keywords: Chalcone; Thermal study; Non-isothermal thermogravimetric analysis; Activation energy